Gender differences in leadership: An integrative approach to explain organizational effectiveness - Lacerda, Teresa Correia de (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
The representation of women on corporate boards and other leading positions has captured the attention of the scholarly community. Several studies have emerged focusing on the impact that a higher number of women on corporate boards would have on board effectiveness and firm performance. However, these studies have failed to identity the differences of gender in effective leadership. This study fills this gap in the literature by investigating those differences at levels ranging from traits to impact on overall organizational effectiveness. For the sake of parsimony, we focused on two levels of mediators that we assumed to be the most theoretically relevant. Previous research gives support to the perspective that trait-like individual differences have a more indirect effect on leadership outcomes, whereas skills and behaviors have a more direct effect (Chan & Drasgow, 2001; DeRue, Nahrgang, Wellman, & Humphrey, 2011; Mumford, Zaccaro, Connelly, & Marks, 2000). By answering the question “What is the impact of leaders differentiated by gender on organizational effectiveness?”, we will capture important insights on gender differences and their impact. Using a quantitative approach, we collected 381 questionnaires from two different samples of corporate leaders to capture their self perceptions on leadership effectiveness. Data was computed by confirmatory factor analysis using structural equation modelling (Partial Least Squares). After assessing the measurement models, we have confirmation for good psychometric properties. To find whether there is a significant difference in the path coefficients between groups, we used PLS-SEM parametric approach to multigroup analysis proposed by Keil et al. (2000). Results show no significant differences between the path coefficients directed to overall organizational effectiveness, across male and female groups. However, women leaders use a different combination of behavioral mechanisms when compared to male leaders. Women leaders use, however a different combination of behavioral mechanisms when compared to male leaders. For instance, men consistently use all four identified effective leadership behaviors (i.e., proximal working relationships, vision articulation & realization, adaptive behaviors, and proactive behaviors), while women use predominantly adaptive and proactive behaviors. These results highlight the relevance of proactive behaviors in female leaders. Surprisingly, women leaders do not exhibit a strong orientation to working relationships. Overall, findings give a substantive empirical support to the effects of effective leadership behaviors on organizational effectiveness, contribute to the theoretical debate on gender differences in leadership behaviors, and help managers understand the impact of gender differences on organizational effectiveness.